Pelatihan Deteksi Dini Stroke “Metode Fast” Pada Lansia di Nagari Jawi- Jawi Kabupaten Solok Sumatera Barat - Rinita Amelia; Dessy Abdullah; Fidiariani Sjaaf; Nadia Purnama Dewi (Jurnal Abdimas ADPI Sains dan Teknologi, 2021)
Stroke is a degenerative disease that often occurs on elderly people. Stroke causes the life quality of elderly people becomes low, in which they will face dependence in various life activities. Fatal and permanent effects due to stroke can be avoided if the patient gets medical services quickly and precisely in 3-5 hours. Usually, this golden period makes stroke quickly overcome and the prognosis is better. FAST is one of stroke early detection methods which is easy to teach and understand for elderly people. FAST stands for Face, Arm, Speech, and Timing. Based on the training and education results, the participants received appreciation from various parties, especially the elderly people in Nagari Jawi-Jawi, Solok Regency, the cadres of the Integrated Services Post, and families with elderlies. Most of the trainees were elderly women aged 61-75 years. The follow-up is a program evaluation that would be carried out by the team of Students Creativity Program in coordination with the local Regional Government to be continued by the cadres of the Integrated Service Post for all the elderly people in Nagari Jawi-Jawi, Solok Regency, and it is also expected that all participants can socialize to their families and surrounding environment about this FAST method.